1999
DOI: 10.3168/jds.s0022-0302(99)75487-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Timed Embryo Transfer with Fresh and Frozen In Vitro Produced Embryos to Increase Pregnancy Rates in Heat-Stressed Dairy Cattle

Abstract: Our objective was to determine whether pregnancy rates in heat-stressed dairy cattle could be enhanced by timed embryo transfer of fresh (nonfrozen) or frozen-thawed in vitro-derived embryos compared to timed insemination. Ovulation in Holstein cows was synchronized by a GnRH injection followed 7 d later by PGF2 alpha and a second treatment with GnRH 48 h later. Control cows (n = 129) were inseminated 16 h (d 0) after the second GnRH injection. On d 7, a fresh (n = 133) or frozen-thawed (n = 142) in vitro-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
2
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 31 publications
9
75
2
13
Order By: Relevance
“…Moreover, IVEP from slaughterhouse material provides a high number of oocytes or embryos (after in vitro maturation and fertilisation) at a low cost to carry out other associated embryo technologies such as cryobiology. In bovine, IVEP is especially interesting to mitigate the decrease in fertility suffered by dairy cattle during environmental heat stress conditions (Ambrose et al, 1999; -E-mail: miguel.silvestre@uv.es Al-Katanani et al, 2002) or to take advantage of the ovum pick-up technique (OPU). In the latter case, a small number of oocytes per female are usually recovered after OPU (approximately three to six oocytes recovered per nonstimulated cow and session; Rizos et al, 2005;Chaubal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IVEP from slaughterhouse material provides a high number of oocytes or embryos (after in vitro maturation and fertilisation) at a low cost to carry out other associated embryo technologies such as cryobiology. In bovine, IVEP is especially interesting to mitigate the decrease in fertility suffered by dairy cattle during environmental heat stress conditions (Ambrose et al, 1999; -E-mail: miguel.silvestre@uv.es Al-Katanani et al, 2002) or to take advantage of the ovum pick-up technique (OPU). In the latter case, a small number of oocytes per female are usually recovered after OPU (approximately three to six oocytes recovered per nonstimulated cow and session; Rizos et al, 2005;Chaubal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A few years earlier, Gilad et al, [4] reported that conception rates in Israel fell from 52% in winter to 24% in the summer. In summer, 80% of estrus may be undetectable [15]. Also indicated, Ryan et al, [22] that when the rectal temperature of the animals increased from 38.5°C to 40°C in 72 hours after insemination service, pregnancy rates can decrease up to 50%.…”
Section: On Fertilitymentioning
confidence: 99%
“…In other studies in Florida, [15] showed that in summer with heat and humidity conditions, pregnancy rates are down to 10%.…”
Section: Types Of Stress Caloricmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides to faster genetic progress, ET also has the potential to increase fertility in dairy cows experiencing heat stress (Putney et al, 1989;Ambrose et al, 1999;Baruselli et al, 2010;Rodrigues et al, 2004Rodrigues et al, , 2007Rodrigues et al, , 2011 and those diagnosed as repeatbreeders (Dochi et al, 2008;Rodrigues et al, 2011), because it bypasses problems associated with fertilization failure and disruption of the oocyte quality in dairy cows (Ferreira et al, , 2016. For example, Baruselli et al 2011, utilizing data from a large commercial herd in Brazil, showed that conception results can be increased in about ~8% (cooler months) to 20% (warmer months) percentage points with the use of ET when compared to AI (Fig.…”
Section: Use Of Moet and Ivp In Dairy Herdsmentioning
confidence: 99%